EFFICACY OF ISCHEMIC STROKE PREVENTION IN PATIENTS WITH IMPLANTED OCCLUDER OF THE LEFT ATRIUM. FIVE YEAR FOLLOW-UP - К. V. Davtyan; A. A. Kalemberg; G. Yu. Simonian; A. G. Topchian; S. N. Koretskiy (Российский кардиологический журнал, 2018)
Aim. In the study we set an aim to evaluate the rate of thromboembolic complications in atrial fibrillation (AF) patients with implanted occluding device of the left atrium appendage (LAA).Material and methods. Beginning at 2012, in the study center, 102 LAA occluders were implanted, of those 44 Watchman device (Boston Scientific), 55 Amplatzer Cardiac Plug (AGA Medical), and 3 Amulet (Abbott). Total follow-up 304,8 patientyears, mean follow-up duration 2,98±1,72 y.Results. During the period, 1 (0,98%) case of acute stroke was registered and 1 case of transient cerebral ischemia. Control transesophageal assessment was done in 100 patients, in 4 (4%) cases there was transient thrombosis of atrial area of the device with no significant outcomes.Conclusion. Implantation of the LAA occluder is an alternative for anticoagulation in AF patients with high thromboembolic and not possible drug prevention.